Evaluation of the performance of a lead-free piezoelectric material for energy harvesting - Machado, Sebastián Pablo (2015)
Vibration-based energy harvesting has been explored as an auxiliary power source, which canprovide small amounts of energy to power remote sensors installed in inaccessible locations.This paper presents an experimental and analytical study of an energy harvesting device using alead-free piezoelectric material based on MoO3-doped (K0.44 0.52 0.04 Na Li )(Nb Ta Sb 0.86 0.10 0.04)O3KNL-(NTS)Mo. The harvesting model corresponds to a cantilever beam with a KNL-(NTS)Mopiezoelectric disc attached to it. We analyze the effect of electromechanical coupling and loadresistance on the generated electrical power. Electromechanical frequency response functionsthat relate the voltage output to the translational base acceleration are shown for experimentaland analytical results.